Peircean Semiotic Analysis of the Film Poster Tuhan Izinkan Aku Berdosa: Representation of Sin and Morality - Shela Kusumaningtyas (Faculty of Law, Universitas Pekalongan, 2025)
Movie posters not only serve as promotional tools but also as visual communication media that convey deep messages related to the themes and values presented in the film. The poster for Tuhan Izinkan Aku Berdosa is particularly interesting to analyze due to its complex use of visual elements and text in representing moral conflict, sin, and redemption. This study aims to identify and analyze the meanings of icons, indexes, and symbols in the film poster using Peircean semiotics. The research employs a qualitative descriptive method with a Peircean semiotic analysis tec nique, which classifies signs into three main categories: icons, indexes, and symbols. The findings reveal that the iconography of the main characters’ faces reflects inner conflict and emotional turmoil, the color index and character positioning depict a spiritual journey and moral value opposition, while the symbolism in the title and golden color represents the moral paradox emphasized in the film. In conclusion, the Tuhan Izinkan Aku Berdosa poster is not merely aesthetic but also rich in meaning, allowing for diverse interpretations among audiences. This study highlights the importance of semiotic analysis in understanding visual communication in film media.